S100A9 Regulates MDSCs-Mediated Immune Suppression via the RAGE and TLR4 Signaling Pathways in Colorectal Carcinoma - Huang, Mao; Wu, Rui; Chen, Lu; Peng, Qi; Li, Shue; Zhang, Yan; Zhou, Lan; Duan, Liang (Frontiers in Immunology, 2019)
Myeloid-derived suppressor cells (MDSCs) are a major component of the immunosuppressive tumor microenvironment (TME) and have been recognized as a contributing factor to inflammation-related cancers. However, the molecular mechanisms of MDSCs accumulation and activation are still elusive. We previously showed that the proinflammatory molecule S100A9 in TME exerts a tumor-promoting effect in colorectal carcinoma (CRC). In this report, we investigated the effect and molecular mechanisms of S100A9 on the accumulation and immunosuppressive function of MDSCs in CRC. Elevated S100A9 and MDSCs were found in tumor tissue and peripheral blood from CRC patients. Circulating S100A9 and MDSCs were positively associated to each other, and both S100A9 and MDSCs were correlated to neoplastic progression. By using a CRC cell line LoVo-induced MDSCs model, we found that S100A9 stimulated chemotaxis and activation but not viability of MDSCs. Mechanistic studies demonstrated that activation of RAGE-mediated p38 MAPK and TLR4-mediated NF-κB signaling pathways was involved in S100A9-induced chemotaxis and MDSCs activation, respectively. Furthermore, ROC analysis showed that combination detection of S100A9 and MDSCs was superior to individual detection of these two factors for diagnosing CRC patients with advanced staging and lymphatic metastasis, which yielded an area under the ROC curve (AUC) of 0.92 with 86.7% sensitivity and 86.4% specificity and an AUC of 0.82 with 75% sensitivity and 77.1% specificity, respectively. Collectively, our study suggests that the S100A9 plays a pivotal role in immunosuppressive TME by stimulating MDSCs chemotaxis and activation, and combination detection of S100A9 and MDSCs may serve as a potential marker for diagnosis of CRC progression.